Painful Terminal Neuroma Prevention by Capping PRGD/PDLLA Conduit in Rat Sciatic Nerves. Issue 6 (27th March 2018) - Yi, Jiling; Jiang, Nan; Li, Binbin; Yan, Qiongjiao; Qiu, Tong; Swaminatha Iyer, Killugudi; Yin, Yixia; Dai, Honglian; Yetisen, Ali K.; Li, Shipu
Abstract: Neuroma formation after amputation as a long‐term deficiency leads to spontaneous neuropathic pain that reduces quality of life of patients. To prevent neuroma formation, capping techniques are implemented as effective treatments. However, an ideal, biocompatible material covering the nerves is an unmet clinical need. In this study, biocompatible characteristics presented by the poly(D, L‐lactic acid)/arginylglycylaspartic acid (RGD peptide) modification of poly{(lactic acid)‐ co ‐ [(glycolic acid)‐alt‐(L‐lysine)]} (PRGD/PDLLA) are evaluated as a nerve conduit. After being capped on the rat sciatic nerve stump in vivo, rodent behaviors and tissue structures are compared via autotomy scoring and histological analyses. The PRGD/PDLLA capped group gains lower autotomy score and improves the recovery, where inflammatory infiltrations and excessive collagen deposition are defeated. Transmission electron microscopy images of the regeneration of myelin sheath in both groups show that abnormal myelination is only present in the uncapped rats. Changes in related genes (MPZ, MBP, MAG, and Krox20) are monitored quantitative real‐time polymerase chain reaction (qRT‐PCR) for mechanism investigation. The PRGD/PDLLA capping conduits not only act as physical barriers to inhibit the invasion of inflammatory infiltration in the scar tissue but also provide a suitable microenvironment for promoting nerve repairing and avoiding neuroma formation during nerve recovery. Abstract : A synthetic polymeric nerve conduit is utilized to prevent traumatic neuroma. The nerve capping conduit allows coordination of the apoptosis and tissue reconstruction. As a consequence, physiological events contributing to neuroma formation and pain irritation, such as excessive inflammation response, collagen deposition, and demyelination in injured nerve stumps, are alleviated.